Sickness Absence Due to Temporary Incapacity for Work. A Review of Current Debates - Crespí Ferriol, Maria del Mar (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
The sustained increase in sickness absence due to temporary incapacity for work has become one of the main challenges currently facing labour relations and the Social Security system in Spain. This article reviews some of the most controversial issues raised by this phenomenon from a twofold perspective. On the one hand, it examines factors related to workers’ health and the preventive strategies associated with occupational health, healthcare provision and return-to-work policies. On the other hand, it analyses the economic incentives and recent legal reforms affecting absence-related decisions, paying particular attention to employment stability and to the impact of Act 15/2022 on protection against dismissal and sickness absence-related pay policies. The analysis highlights the complementary nature of both perspectives and the limitations of considering either of them in isolation.
Keywords: Sickness absence; Temporary incapacity for work; Occupational health; Return to work; Economic incentives